2022
DOI: 10.32604/cmc.2022.025636
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Band Metamaterial Inspired Antenna for Future Terahertz (THz) Applications

Abstract: For future healthcare in the terahertz (THz) band, a triple-band microstrip planar antenna integrated with metamaterial (MTM) based on a polyimide substrate is presented. The frequencies of operation are 500, 600, and 880 GHz. The triple-band capability is accomplished by etching metamaterial on the patch without affecting the overall antenna size. Instead of a partial ground plane, a full ground plane is used as a buffer to shield the body from back radiation emitted by the antenna. The overall dimension of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…With the help of flawed ground structures, mutual coupling between the MIMO antennas can be reduced, even when they are placed laterally [ 7 ]. A triple-band MPA built on a polyimide substrate and integrated with a metamaterial has been presented as a potential solution for future healthcare applications in the terahertz band [ 8 ]. An antenna with a tunable resonance frequency via an external voltage was presented through the use of a graphene material.…”
Section: Introductionmentioning
confidence: 99%
“…With the help of flawed ground structures, mutual coupling between the MIMO antennas can be reduced, even when they are placed laterally [ 7 ]. A triple-band MPA built on a polyimide substrate and integrated with a metamaterial has been presented as a potential solution for future healthcare applications in the terahertz band [ 8 ]. An antenna with a tunable resonance frequency via an external voltage was presented through the use of a graphene material.…”
Section: Introductionmentioning
confidence: 99%
“…Mathur, R. S. Sharma, 2018) discussed the devastating effect of exposure to EMR at RF in short and long range and concluded that it may leads to cancer and DNA alteration. Also, Ashyap et, al (Ashyap et al, 2020) pointed out that wave propagation around human body is interfered due to complex electromagnetic properties of the body. The interference may have an adverse effect on human health (Natarajan & Babu, 2019).…”
Section: Introduction 11 Introductionmentioning
confidence: 99%